2014
DOI: 10.1117/12.2041446
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating the growth phases of single bacteria using Raman spectroscopy

Abstract: In this paper we present a longitudinal study of bacteria metabolism performed with a novel Raman spectrometer system. Longitudinal study is possible with our Raman setup since the overall procedure to localize a single bacterium and collect a Raman spectrum lasts only 1 minute. Localization and detection of single bacteria are performed by means of lensfree imaging, whereas Raman signal (from 600 to 3200 cm -1 ) is collected into a prototype spectrometer that allows high light throughput (HTVS technology, Tor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…These results maintain a good correlation with the results of the ATR analysis. The differences in Raman spectra between bacteria in different growth phases were previously reported [ 24 , 25 ]. In particular, a decrease in Raman bands related to nucleic acids (1484, 783 cm −1 ) in the log phase compared to lag phase was observed [ 25 ].…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…These results maintain a good correlation with the results of the ATR analysis. The differences in Raman spectra between bacteria in different growth phases were previously reported [ 24 , 25 ]. In particular, a decrease in Raman bands related to nucleic acids (1484, 783 cm −1 ) in the log phase compared to lag phase was observed [ 25 ].…”
Section: Resultsmentioning
confidence: 58%
“…In particular, a decrease in Raman bands related to nucleic acids (1484, 783 cm −1 ) in the log phase compared to lag phase was observed [ 25 ]. This were attributed to changes in relative nucleic acids and protein content between various growth phases [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to perform an external validation, the influence of important factors like growing time, or nutrition, or matrix (sterile or real) effects need to be taken into account in the dataset. For instance, we already observed that our system can discriminate between different growth phases of E. coli and B. subtilis bacteria based on Raman analysis 24 . Next work will be then to build a reliable dataset comprising these different parameters, and to investigate how scattering patterns collected using the lensfree module can help the identification of bacteria strains.…”
Section: Resultsmentioning
confidence: 97%
“…It would also allow, if necessary, to guide the choice for further analyses. Among the technologies capable of rapidly analyzing whole colonies on a Petri dish in a nondestructive way, label-free optical methods, such as Raman spectroscopy 7 , elastic light scattering 8,9 or Fourier-transformed infrared spectroscopy (FTIR) 10 are of particular interest. Specifically, infrared spectroscopy is one of the oldest label-free optical identification technologies 11 .…”
Section: Introductionmentioning
confidence: 99%